Hsa-miR-323a-3p functions as a tumor suppressor and targets STAT3 in neuroblastoma cells - Bhavsar, Swapnil Parashram; Olsen, Lotte; Løkke, Cecilie; Koster, Jan; Flægstad, Trond; Einvik, Christer (Frontiers in Pediatrics, 2023)
Background: Studies conducted the last decades have revealed a role for the non-coding microRNAs (miRNAs) in cancer development and progression. Several miRNAs within the chromosome region 14q32, a region commonly deleted in cancers, are associated with poor clinical outcome in the childhood cancer - neuroblastoma. We have previously identified miR-323a-3p from this region to be downregulated in chemotherapy treated neuroblastoma cells compared to pre-treatment cells from the same patients. Furthermore, in neuroblastoma tumors, this miRNA is downregulated in advanced stage 4 disease compared to stage 1-2. In this study, we attempt to delineate the unknown functional roles of miR-323a-3p in neuroblastoma. Methods: Synthetic miRNA mimics were used to overexpress miR-323a-3p in neuroblastoma cell lines. To investigate the functional roles of miR-323a-3p, cell viability assay, flow cytometry, reverse transcription-quantitative polymerase chain reaction, luciferase reporter assay and western blot were conducted on the neuroblastoma cell lines Kelly, SH-SY5Y and SK-N-BE(2)-C. Results: Ectopic expression of miR-323a-3p resulted in marked reduction of cell viability in Kelly, SH-SY5Y and SK-N-BE(2)-C by causing G1-cell cycle arrest in Kelly and SH-SY5Y and apoptosis in all the cell lines tested. Furthermore, mRNA and protein levels of signal transducer and activator of transcription 3 (STAT3) were reduced upon miR-323a-3p overexpression. A direct binding of the miR-323a-3p to the 3’UTR of STAT3 was experimentally validated by luciferase reporter assay, where miR-323a-3p reduced luminescent signal from full length STAT3 3’UTR luciferase reporter, but not from a reporter with mutation in the predicted seed sequence. Conclusions: miR-323a-3p inhibits growth of neuroblastoma cell lines through G1-cell cycle arrest and apoptosis, and the well-known oncogene STAT3 is a direct target of this miRNA.